PENINGKATAN KEMAMPUAN MENULIS SURAT RESMI SISWA KELAS XI SMK NEGERI 2 KOTA TERNATE - Justam Wahab (Jurnal Bilingual, 2022)
Letters are a medium of communication in written form carried out by a person or institution addressed to another person or institution. Definition of Letter, Official Letter 1. Use letterhead if issued by the organization; 2. There is a letter number, attachment, and subject matter; 3. Using the usual opening and closing greetings; 4. Use of various official languages; 5. Include a stamp or seal from an official institution; 6. There are standard format rules. Job Application Letter, Job application letter is a letter made by someone (applicant) addressed to a particular office or company in order to get a job in accordance with the job vacancy offered. Licensing Letter, Licensing Letter is a letter written by someone whose contents concern a request for permission from a certain party to obtain the intended permit. In addition to a personal letter to an agency or office where one works, a permit is also needed to obtain permission from certain parties if a person or a family wants to hold an activity or a crowd in the community, this is intended so that if something unexpected happens that party can take responsibility. The main reason letters are still needed is because we need documents for every business and official activity that is carried out. Written notes will never be replaced by oral communication, although oral documentation with memory in computerized systems is growing rapidly. Letters will be a vital part as long as modern culture and civilization are still running as usual. From the description above, the functions of a letter include: 1. The most accurate reminder tool, because it can be interpreted and can be read again when needed; 2. Black and white evidence, especially a letter of agreement; 3. Documents; 4. Representative/ambassador of the author for readers; 5. Work guidelines, for example decrees, instructions, assignment letters, and so on; 6. Aspects of public relations, because it has an impact on fostering good relations between an institution and its public. In preparing official letters properly and correctly, using several approaches, namely (1) drafting the letter must understand the purpose of making the letter, (2) whether the preparation of the letter is to seek or provide information, and (3) provide decisions, assignments, or reports, submit solicitation, application, offer or order. Letters are an important means of communication.